Research of temperature deformations of selflubricating tapered bearings of low-consumption rotor units - N. A. Raykovskiy; V. L. Yusha; A. V. Tretyakov; V. A. Zakharov; K. I. Kuznetsov (Омский научный вестник)
The use of self-lubricating bearing units of conical shape implemented according to the «rotaprint» lubrication scheme is promising in oil-free small-sized turbine units to provide a given resource. At the same time, an important issue, especially for microturbines, is to ensure the required temperature regimes and permissible temperature deformations. The paper proposes a numerical method for calculating the conical bearing units implemented under the scheme «rotaprint» with a different number of smearing elements, which takes into account the mutual influence of the operating modes of the turbine unit and the cooling system of the bearing. The method consists of two stages: the first one defines the temperature fields, then the results are transferred as the initial data for the second stage – the definition of the fields of thermal deformation. The results of the deformation calculation serve as the initial data for the thermal calculation of the adjusted geometric dimensions, thus an iterative calculation to the desired convergence. The approbation is performed and the results of the analysis of the temperature state and temperature deformations for different angles of the cone of the bearing unit with different number of smearing elements in relation to the bearings both on the compressor side and on the turbine side in their cantilever execution are presented.